Development of a Potential Yeast-Based Vaccine Platform for Theileria parva Infection in Cattle - Goh, Shan; Kolakowski, Jeannine; Holder, Angela; Pfuhl, Mark; Ngugi, Daniel; Ballingall, Keith; Tombacz, Kata; Werling, Dirk (Frontiers in Immunology, 2021)
East Coast Fever (ECF), caused by the tick-borne apicomplexan parasite Theileria parva, remains one of the most important livestock diseases in sub-Saharan Africa with more than 1 million cattle dying from infection every year. Disease prevention relies on the so-called “Infection and Treatment Method” (ITM), which is costly, complex, laborious, difficult to standardise on a commercial scale and results in a parasite strain specific, MHC class I restricted cytotoxic T cell response. We therefore attempted to develop a safe, affordable, stable, orally applicable and potent subunit vaccine for ECF using five different T. parva schizont antigens (Tp1, Tp2, Tp9, Tp10 and N36) and Saccharomyces cerevisiae as an expression platform. Full-length native Tp2 and Tp9 as well as fragments of native Tp1 were successfully expressed on the surface of S. cerevisiae. In vitro analyses highlighted that recombinant yeast expressing Tp2 can elicit IFNy responses using PBMCs from ITM-animals, while Tp2 and Tp9 induced IFNy responses from enriched bovine CD8+ T cells. A subsequent in vivo study showed that oral administration of heat-inactivated, freeze-dried yeast stably expressing Tp2 increased total murine serum IgG over time, but more importantly, induce Tp2 specific serum IgG antibodies in individual mice compared to the control group. While these results will require subsequent experiments to verify induction of protection in neonatal calves, our data indicates that oral application of yeast expressing Theileria antigens could provide an affordable and easy vaccination platform for sub-Saharan Africa. Evaluation of antigen specific cellular immune responses, especially cytotoxic CD8+ T cell immunity in cows will further contribute to the development of a yeast-based vaccine for ECF.